Curriculum Alignment Based on Comprehensive Assessment to Address Reading Difficulties in Inclusive Elementary Classrooms - Hana Qurrotul Uyun; Budi Susetyo; Iding Tarsidi; Tati Hernawati; Ajeng Suryani (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2026)
This study was motivated by students' reading difficulties in inclusive classrooms and the limited implementation of differentiated learning within the Merdeka Curriculum. The study aimed to describe the outcomes of academic and developmental assessments of students with reading difficulties, analyze factors influencing reading challenges, and develop curriculum alignment based on these assessments. This study used a qualitative case study design. The study focused on a first-grade student in an inclusive elementary school who exhibited persistent reading difficulties. Data were obtained from multiple sources, including classroom teachers, school principals, and the student, through observations, in-depth interviews, academic and developmental assessments, and documentation. The collected data were analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings revealed that reading difficulties were influenced by phonological, cognitive, motor, and emotional factors. Curriculum alignment based on comprehensive assessment resulted in more realistic learning objectives, structured instructional strategies, and increased student engagement. The study concludes that comprehensive assessment plays a crucial role as a foundation for curriculum alignment to support effective reading instruction in inclusive elementary classrooms.